Trends now changing the world: economics and society, values and concerns, energy and environment. - Cetron, Marvin J.; Davies, Owen (Futurist)
In an article excerpted from the report “50 Trends Now Changing the World,” the authors present their projections for major trends affecting the world, offering a succinct conclusion about the implications of each for the future and its possible affect on individuals and organizations. The trends discussed are long-term economic and societal trends, trends in values and concerns, energy trends, and environmental trends.